Predictive Direct Power Control (PDPC) of Grid-connected Dual-active Bridge Multilevel Inverter (DABMI) - H.H. Goh; Azuwien Aida; S.S. Lee; S.Y. Sim; K.C. Goh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper deals with controlling a grid-connected dual-active bridge multilevel inverter for renewable energy integration. The concept of direct power control is integrated with model predictive control algorithm, which is termed as predictive direct power control, to control the real and reactive power injected into the power grid. The proposed multilevel inverter allows more options of feasible voltage vectors for switching vector selections in order to generate multilevel outputs, and thereby obtaining high power quality in the power grid. By using the predictive direct power control, simulation results show that the proposed multilevel inverter produces lower power ripple and manage to achieve currents with low total harmonic distortion which are well within the IEEE standard. The modeling and simulation of the system are implemented and validated by MATLAB Simulink software.